2013
DOI: 10.1186/1476-4598-12-116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and evaluation of a novel inhibitor of WNT/β-catenin signaling pathway

Abstract: BackgroundWnt/β-catenin signaling is a highly conserved pathway in organism evolution and is important in many biological processes. Overactivation of Wnt/β-catenin signaling is closely related to tumor development and progression. To identify potent small molecules that can fight aberrant Wnt/β-catenin-mediated cancer, we synthesized a novel pyrazoline derivative (N-(4-hydroxybenzyl)-1,3,4-triphenyl-4,5-dihydro-1H-pyrazole-5-carboxamide, BHX) to block Wnt signaling, and determined the absolute configuration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…BHX, a novel low molecular weight pyrazoline derivative, was previously synthesized in our laboratory. We have demonstrated that BHX exhibits cytotoxic effects in multiple solid tumour cell lines, including A549, HT29, and MGC803 15 . In the present study, we have further verified that BHX suppresses not only cell viability but also cell migration and invasion, and induces cell cycle G1 phase arrest.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…BHX, a novel low molecular weight pyrazoline derivative, was previously synthesized in our laboratory. We have demonstrated that BHX exhibits cytotoxic effects in multiple solid tumour cell lines, including A549, HT29, and MGC803 15 . In the present study, we have further verified that BHX suppresses not only cell viability but also cell migration and invasion, and induces cell cycle G1 phase arrest.…”
Section: Discussionmentioning
confidence: 96%
“…PVDF membranes were supplied by Millipore (Billerica, MA, USA). BHX was synthesized as previously described 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that drugs and inhibitors targeting this pathway may have clinical potential in the treatment of prostate cancer. Various inhibitors are currently at developmental stages (29)(30)(31)(32), however require further evaluation regarding their role in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The novel pyrazoline derivative, N ‐(4‐hydroxybenzyl)‐1,3,4‐triphenyl ‐4,5‐dihydro‐1 H ‐pyrazole‐5‐carboxamide (BHX), designed and synthesized previously, has been described to block the canonical Wnt/β‐catenin signalling pathway, and has been reported to exhibit cytotoxic effects in multiple solid tumour cell lines . However, the anti‐proliferative effects of BHX on leukaemia cells have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%